(untitled) (Bangladesh Journal of Psychiatry, 2020)
Irritable Bowel Syndrome (IBS) is a functional disorder characterized by a set of gastrointestinal symptoms often associated with extra-digestive symptoms with unknown organic basis. It is a prototypic functional bowel disorder in terms of its heterogeneous nature with multifactor pathogenesis. Invariably it is co-morbid with psychiatric disorders. This study was done to determine the frequency and types of psychiatric disorders with irritable bowel syndrome and to find out association of socio-demographic and relevant variables. It was cross-sectional study carried out in the Department of Gastroenterology, Bangabandhu Sheikh Mujib Medical University (BSMMU) from January 2014 to December 2014. Total 250 sample were included by convenient sampling technique in this study diagnosed as IBS. Diagnosis was done according to Rome III criteria and SCID-CV was used for psychiatric assessment. Respondents were above 18 years of age of either sex. Data was analyzed using SPSS 20. Results showed 86.4% patients have psychiatric disorders. The most common disorder was generalized anxiety disorder (44.9%) followed by major depressive disorder (37.5%). Maximum (35.2%) were IBS-D type followed by 32.8% IBS-C type and 32% IBS-M type. So, it is seen that significant proportion of psychiatric disorders was found in patients with irritable bowel syndrome. Among them, generalized anxiety disorder was leading psychiatric disorder. Bang J Psychiatry 2018;32(2): 32-36